A DFT Study on the Excited Electronic States of Cyanopolyynes: Benchmarks and Applications - Marcin Gronowski; Robert Kołos (Molecules, 2022)
Highly unsaturated chain molecules are interesting due to their potential application as nanowires and occurrence in interstellar space. Here, we focus on predicting the electronic spectra of polyynic nitriles HC2m+1N (m = 0–13) and dinitriles NC2n+2N (n = 0–14). The results of time-dependent density functional theory (TD-DFT) calculations are compared with the available gas-phase and noble gas matrix experimental data. We assessed the performance of fifteen functionals and five basis sets for reproducing (i) vibrationless electronic excitation energies and (ii) vibrational frequencies in the singlet excited states. We found that the basis sets of at least triple-ζ quality were necessary to describe the long molecules with alternate single and triple bonds. Vibrational frequency scaling factors are similar for the ground and excited states. The benchmarked spectroscopic parameters were shown to be acceptably reproduced with adequately chosen functionals, in particular ωB97X, CAM-B3LYP, B3LYP, B971, and B972. Select functionals were applied to study the electronic excitation of molecules up to HC27N and C30N2. It is demonstrated that optical excitation leads to a shift from the polyyne- to a cumulene-like electronic structure.